PENGANGGARAN BIAYA BAHAN PAKAN DAN PENJUALAN TELUR (P.O KINANTAN DI KENAGARIAN PILUBANG KECAMATAN HARAU KABUPATEN LIMA PULUH KOTA) - Andria Ningsih (Jurnal Praktik Bisnis, 2016)
Eggs are the harvest of raising chickens who become daily human needs. So to meet human needs, it takes the eggs that have good quality. the price of feed is a major influence on the sale of chicken eggs. One poultry farm is P.O KinantanKenagarianPilubang District of Harau District Fifty State. Feed prices are unstable. If feed prices rose, while the price of eggs in the market selling cheap, can lead to a slump in sales of eggs in the market so that employers laying chickens suffered heavy losses. Budget cost of feed materials will go up if the amount of the chicken population was growing and stable feed prices, and vice versa feedstuffs budget will decrease if the number of chicken population decline due to rising feed prices. Sales of eggs in P.O Kinantanin KenagarianPilubang Districtof Harau District Fifty Cities. Keywords: Budget costs and Sales